2019
DOI: 10.1159/000496846
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Adrenal Function after Pituitary Surgery in Patients with Cushing Disease: Persistent Remission or Recurrence?

Abstract: Background: Cushing disease (CD) represents the principal cause of endogenous hypercortisolism. The first-line therapy of CD is surgical removal of the ACTH-secreting pituitary adenoma, which is generally followed by adrenal insufficiency (AI). Objective: To analyze the recovery of AI in patients with CD after pituitary surgery in relation with recurrence and persistent remission of CD. Patients and Methods: We performed a retrospective analysis of patients with CD who met the following inclusion criteria: adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Furthermore, the range of the reported median time to recovery varies between various cohorts (ranging from 6 months to more than 2 years). Of note, what has been more commonly reported is the association of early HPA axis recovery with higher risk for CD recurrence 5,7 . However, only one study, from our centre, has previously described the HPA axis recovery in paediatric patients, who may behave differently than adults due to varying sensitivity or maturation of the HPA axis, and this prior study because of its lower numbers did not allow for a meaningful statistical analysis of risk for recurrence 10 …”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, the range of the reported median time to recovery varies between various cohorts (ranging from 6 months to more than 2 years). Of note, what has been more commonly reported is the association of early HPA axis recovery with higher risk for CD recurrence 5,7 . However, only one study, from our centre, has previously described the HPA axis recovery in paediatric patients, who may behave differently than adults due to varying sensitivity or maturation of the HPA axis, and this prior study because of its lower numbers did not allow for a meaningful statistical analysis of risk for recurrence 10 …”
Section: Introductionmentioning
confidence: 91%
“…Previous studies have shown increased risk for recurrence with earlier recovery in adult patients, but this has not been reported previously in the paediatric population. 5,25 In adults with recurrence, recovery of the [26][27][28] The most recent meta-analysis included 30 studies of patients with secondary AI and showed no statistical difference in the diagnostic accuracy of the two tests, although both test showed low sensitivity. 26 Given the technical difficulties in performance of a low-dose test, in our institute, we have been performing only standard-dose testing for our patients.…”
Section: Characteristics Of Patients With and Without Recurrencementioning
confidence: 99%
See 3 more Smart Citations